if (x+iy)(2-3i)=4+i then find (x,y)

 2x - 3ix + 2iy - 3i square y = 4 + i

(2x + 3y) + i( -3x + 2y) = 4  + i   ( becuz i square = -1)

comparing real nd imaginary parts we get..

3(2x + 3y = 4 ) 

2(-3x + 2y = 1)

--------------------

6x + 9y = 12

-6x + 6y = 2

now,

15y = 14

y = 14/15

now, put the value of y in eq... 1

2x + 3y = 4

2x + 3 * 14/15 = 4

2x + 14/5 = 4

2x = 4 - 14/5

2x = 20 - 14 / 5

2x = 6/5

x = 6/5 * 1/2

x = 3/5  ans..

  • -15
HOW DID 2X2Y BECOME 6Y?
 
  • -13
Why is this question unattended?
 
  • -10
HOPE IT WILL HELP YOU FOR SOLVING THE PROBLEM

  • -3
(X+Yi)(2-3i)= 4+I Take the 2-3i to the right side 4-i/2-3i Rationalize the denominator by multiplying by 2+3i Now you should get 5+14i/13 Rewrite as 5/13+14i/13 Now just compare with x+Yi Thus X=5/13 Y=14/13

  • 1
What are you looking for?